Household Waste Management Through a Waste Bank System to Increase Household Income for Residents of Dukuh Pondok Serang Mulur - Fitria, Tira Nur (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Waste management in villages is becoming an increasingly important challenge to pay attention to. Communities often face problems in sorting and managing waste, which has an impact on the environment and health. To overcome this problem, community service activities through the Waste Bank concept were introduced. This activity aims to increase public awareness, especially among housewives, about the importance of waste management through waste banks and provide economic opportunities for well-managed waste. This activity was held on Saturday, 21 September 2024 in Pondok Serang Mulur Sukoharjo and involved representatives of the residents as future managers of the Waste Bank. The activity began with lectures and demonstrations regarding waste management, its impact on the environment, and the importance of waste banks so that residents were more motivated to participate. Furthermore, direct practice was carried out on how to sort waste based on type such as non-organic waste including plastic, glass, cardboard, mineral water bottles, plastic bags, and food packaging. Paper, iron, and electronic goods provide a concrete experience so that residents can apply this technique at home before taking the waste to the waste bank. After sorting, residents weigh each type of waste collected and record the price per kilo according to type, so that they understand the economic value of waste and are motivated to collect more. All types of waste are then collected into large plastic bags at the waste bank location to wait to be transported by waste vans, ensuring that management is carried out efficiently. At the end of the activity, discussions and evaluations were held to formulate follow-up plans, including regular meetings to monitor progress, so that the waste management program could be sustainable and effective. Thus, it is hoped that this activity can create a more structured waste management system, increase community participation, and provide environmental and economic benefits for the community. The response from participants in community service activities regarding waste management through waste banks was generally enthusiastic and positive. The resident felt enthusiastic about the new knowledge regarding the importance of sorting and managing waste, as well as being aware of its impact on the environment. They appreciated the hands-on practice that allowed them to learn how to sort organic and non-organic waste, and many committed to being more disciplined in waste management at home. Participants also hope that similar activities can be held regularly to continue to increase knowledge and share experiences. Several inputs were submitted regarding improving waste bank facilities and the need for further outreach regarding the economic value of waste. Overall, participants felt this activity was useful and wanted to contribute more to waste management in their community.